2008
DOI: 10.1186/1475-2891-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Ketogenic Mediterranean diet: a healthy cardiovascular diet for weight loss

Abstract: Background: Ketogenic diets are an effective healthy way of losing weight since they promote a non-atherogenic lipid profile, lower blood pressure and decrease resistance to insulin with an improvement in blood levels of glucose and insulin. On the other hand, Mediterranean diet is well known to be one of the healthiest diets, being the basic ingredients of such diet the olive oil, red wine and vegetables. In Spain the fish is an important component of such diet. The objective of this study was to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 37 publications
4
61
1
3
Order By: Relevance
“…Salas Salvado et al [2008] reported that after consumption of 1 L/week of olive oil for one year in hyperlipidemic subjects, lower incidence of elevated TAG was seen. In another study with Mediterranean diet including olive oil as the principal source of fat for 12 weeks TC and TAG levels were reduced [Perez-Guisado et al, 2008]. Our results are not consistent with observations of Salas Salvado et al [2008] and Perez-Guisado et al [2008], which at a higher amount of olive oil and longer study period resulted in a reduction of TC and TAG.…”
Section: Resultscontrasting
confidence: 99%
“…Salas Salvado et al [2008] reported that after consumption of 1 L/week of olive oil for one year in hyperlipidemic subjects, lower incidence of elevated TAG was seen. In another study with Mediterranean diet including olive oil as the principal source of fat for 12 weeks TC and TAG levels were reduced [Perez-Guisado et al, 2008]. Our results are not consistent with observations of Salas Salvado et al [2008] and Perez-Guisado et al [2008], which at a higher amount of olive oil and longer study period resulted in a reduction of TC and TAG.…”
Section: Resultscontrasting
confidence: 99%
“…48,49,50,51,52,53 Studies are also now emerging to show the efficacy, sustainability and other positive effects of lowcarbohydrate diets, especially in those with metabolic disease. 54,55,56,57,58,59,60,61 The definition of a low-carbohydrate diet varies in the literature, but most in the field agree that anything over 130 g -150 g per day is not low carbohydrate. 62 An amount of less than 50 g of carbohydrate per day is considered very low carbohydrate, which would put most adults into nutritional ketosis.…”
Section: Trials Of Low-carbohydrate Diets: Significant Findings For Amentioning
confidence: 99%
“…In obese individuals [149] and healthy subjects who underwent eccentric exercise training [150], the inflammatory state was further augmented postprandially through a high CHO intake, but not through high-fat, low CHO meals in the latter study. Maybe more importantly, even moderate CHO restriction has been shown to effectively target several important markers of atherosclerosis and type II diabetes, both of which are associated with chronic inflammation [151][152][153][154][155][156][157]. Forsythe et al showed that in overweight individuals with dyslipidemia a very low CHO diet had a more favorable effect than a low fat diet in reducing several markers of inflammation [158].…”
Section: Avoidance Of Chronic Inflammationmentioning
confidence: 99%